Strategi Guru dalam Mengembangkan Kecerdasan Emosional Anak di TK Islam Rabbani Batubara - Saanatun, Saanatun; Lubis, Sofni Indah Arifa (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Emotional intelligence in early childhood is very important to provide stimulus, because both directly and indirectly it will influence children's behavior in carrying out activities. Directly, a child's emotional development will determine the child's social skills. This research aims to find out what strategies teachers use in developing children's emotional intelligence at Rabbani Islamic Kindergarten and what factors support and hinder teachers in developing children's emotional intelligence. This research is qualitative research with active, participatory involvement of researchers at the research location in collecting data through participant observation and in-depth interviews. The research results show that the strategy used by teachers is to apply the 5S culture (smile, greet, greet, be polite and courteous) with the storytelling method. Apply validation of feeling stamps (happy, sad, angry, sleepy and others) in the morning before the activity starts. Supporting factors in developing children's emotional intelligence are the availability of play infrastructure and the support of some parents in controlling children's emotions. Meanwhile, the obstacles are differences in character and the gap between what teachers introduce and what parents implement at home. Emotional intelligence will develop when the environment participates in monitoring children's activities.